Pemikiran Ibnu Qasim Al-Ghazi Tentang Pendidikan Ibadah Anak dalam Kitab Fathul Qorib - Khosiin, Nur; Ni’mah, Faizzatin (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Ibnu Qasim Al-Ghazzi is a Muslim scholar, his thoughts on children's religious education in the book Fathul Qorib have made a major contribution to the world of Islamic education, especially for children's education. This type of research is library research. Data collection is carried out using documentation. According to him, worship includes everything that is loved and approved by Allah, whether in the form of words, physical and spiritual actions. Such as: ablution, prayer, zakat, fasting, Hajj and Umrah. The results of this research show that children's religious education in the Fathul Qorib book is explained clearly and completely, so that it is easy for teachers and parents to understand, which can then be taught and practiced to their children/students. Meanwhile, the analysis carried out by researchers shows that the worship education in the book Fathul Qorib is in accordance with the level of religious development in children and is in accordance with the religious characteristics of children, namely imitative.